Investigation of Iris, Leptin, Ghreline and Some Hormonal Responses of the Strength Training Program Applied to Handball Players - Turgut, Mine; Cinar, Fidan; Dundar, Aykut; Yasul, Yavuz; Cinar, Vedat; Yamaner, Yusuf Burak (Lahore Medical Research Center Llp, 2021)
Background: The effects of exercise on physiological systems were an inevitable truth. Especially the relationship of exercise with the endocrine system was one of the important focuses of interest. Irisin, Seratonin, Melatonin, Leptin, Ghrelin and Apelin hormones, which become a ball of interest recently, were the subjects that researchers follow and work with great interest. Aim: This study aimed to determine the effect of strength training program applied to handball players on the Irisin, Seratonin, Melatonin, Leptin, Ghrelin and Apelin hormones. Method: 24 healthy male handball players between the ages of 18-24 participated in the study. Participants were randomly divided into two groups (control and experimental). While handball training was applied to the first group (control) for 6 weeks, strength training was applied to the second group (experimental). The blood samples of the participants were taken on an empty stomach in the morning by experts in the appropriate laboratory environment before the training at rest, according to the pre-test and post-test model. In the analysis of the data, descriptive statistics (mean, standard deviation) and Shapiro Wilk test, kurtosis, steepness and histogram graph were taken into consideration to test the normality of the distribution before starting the analysis, and it was observed that the distribution was normal. In this context, Paired Samples t-test was used to reveal intra-group differences and the Independent samples t-test statistical techniques were used to reveal differences between groups. The level of significance was set at 0.05 and the analyses were made in the Windows SPSS 22 package program. Results: It was observed that irisin, apelin and ghrelin levels increased in the experimental group of the strength training program applied with the obtained results, it did not change in the control group. It was determined that the serotonin level increased in both the strength training group and the control group. While it was observed that the leptin level decreased in the Strength group, it did not change in the control group, and it was understood that the melatonin level did not undergo any change in both the experimental and control groups. Conclusion: As a result, it was concluded that the 6-week strength training protocol applied to athletes caused significant changes in irisin, apelin, ghrelin, serotonin, leptin levels of handball players, but did not show any change in melatonin levels.
Keywords: Leptin; Ghrelin; irisin; Strength and Handball